Insomnio en usuarios de pantallas emisoras de luz azul (Salud, Arte y Cuidado, 2026)
The objective of this research was to characterize insomnia in people over fifteen years of age who use blue light-emitting screens and attend the “Don Felipe Ponte” type III urban clinic during the period June-December 2023, through cross-sectional descriptive research. Data collection was carried out by applying an instrument consisting of eleven closed questions to identify the most used blue light-emitting devices, the time of use, and the presence of insomnia. As important results, it was obtained that the largest age group is over 55 years of age, and it is the group that uses more than two blue light-emitting devices. It is also the group that presents the most insomnia, this being chronic. This research seeks to create a precedent in the study of the presence of insomnia and the use of blue light-emitting devices that serve as objective data for future research and that, in addition, can be used to raise awareness and prevent insomnia in the population.
Keywords: electronic devices; blue light; insomnia